(untitled) (Horizontes de Enfermería, 2025)
This study addresses the biomechanical risk present in the activities performed by workers in the operational process of the Cooperativa Empresarial de Recicladores de Nariño E.S.P. (Coemprender) in the city of Pasto, Department of Nariño (Colombia). The objective was to identify and assess the biomechanical risk factors to which these workers are exposed during their daily work activities. A descriptive quantitative methodology was employed, utilizing the technique of quantitative observation, which allowed for the collection of precise and measurable data on postures, repetitive movements, physical exertion, and load handling performed by the workers in their daily routines. Data collection included the use of the Colombian Technical Guide GTC 45, version 2012, ensuring the reliability and validity of the results obtained. The study’s findings revealed that Coemprender workers are exposed to various biomechanical risk factors, such as heavy load lifting, forced postures, and repetitive movements. These factors were quantified and analyzed to determine their risk levels. Thus, the study underscores the need for continuous evaluation of biomechanical risks in the recycling sector, aiming to create a safer and healthier work environment for the workers. Additionally, it highlights the importance of involving the workers themselves in the process of identifying and mitigating risks, thereby fostering a culture of occupational safety and health within the cooperative.